Sistem Pendukung Keputusan Pemilihan Jenis Kayu Terbaik untuk Industri Meubel di Kabupaten TTU dengan Metode Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) - Jekrit Rinto Tefi; Darsono Nababan; Yoseph Pius Kurniawan Kelen; Leonard Peter Gelu (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Selecting the right type of wood is a crucial factor in the furniture industry to produce strong, durable, and quality products. Lack of knowledge in determining the best type of wood often causes furniture production to be less than optimal. This study aims to build a web-based Decision Support System (DSS) that helps furniture entrepreneurs in North Central Timor Regency in selecting the best type of wood using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The criteria used in the selection process are the physical properties of wood, wood durability, wood mechanical properties, wood diameter, and wood texture. The wood alternatives evaluated include mahogany, acacia, angsana, and white teak. The results showed that mahogany obtained the highest value with a score of 0.691, so it is recommended as the best choice. This system is expected to be an effective tool for furniture entrepreneurs in making decisions more systematically and objectively.